Saving Mr. Banks - Hancock, John Lee; Marcell, Kelly; Smith, Sue; Owen, Alson; Thompson, Emma; Hanks, Tom; Walt Disney Pictures (Burbank, California : Disney, 2014)
Determined to fulfill a promise to his daughters, Walt Disney tries for twenty years to obtain the rights to author P.L. Travers beloved book. Armed with his iconic creative vision, Walt pulls out all the stops, but the uncompromising Travers won't budge. Only when he reaches into his own complicated childhood does Walt discover the truth about the ghosts that haunt Travers, and together, they set Mary Poppins free!.
Not all technical specifications apply to all elements. Some content may not be subtitled. Some players may not be able to access all features. Dual-Layer format. Layer transition may trigger a slight pause.
Music by Thomas Newman ; film editor, Mark Livolsi ; director of photography, John Schwartzman.
Emma Thompson, Tom Hanks, Paul Giamatti, Jason Schwartzman, Bradley Whitford, Colin Farrell.
LPF: P13
DVD format, Dual-Layer format, Stereo 2.0, Digitally Mastered.
In English ; English embedded subtitles.
Keywords: Travers, P. L. -- 1899-1996 -- Drama; Disney, Walt, -- 1901-1966 -- Drama; Motion picture industry -- Drama; Motion pictures -- Production and direction -- Drama; Biographical films